Validation test of Indonesian pelvic floor distress inventory-20 (Indonesian PFDI-20) - Pangastuti, Nuring; Iman, Santoso Budi; Denny, Agustiningsih; Emilia, Ova (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
The pelvic floor distress inventory-20 (PFDI-20) questionnaire is one of the questionnaires used to help find out complaints of pelvic floor dysfunction. The questionnaire is also frequently used in studies related to pelvic floor dysfunction. The validation test results of the questionnaire have not been obtained from Indonesian population.This study aimed to obtain an Indonesian PFDI-20 questionnaire that is in accordance with the original questionnaire and valid as well as reliable use for the Indonesian population.The validation test series were conducted through several stages: forward translation, back-translation, expert panel, pre-testing, and cognitive interviewing, final version and documentation. Data of 77 female respondents of reproductive age in the Yogyakarta Special Region were collected from January to March 2018.The statistical test result of questionnaire validity from the corrected item-total correlation of each question item has value more than 0.30 (0.385-0.781) indicating that the Indonesian PFDI-20 questionnaire was valid. Test reliability of the questionnaire using Cronbach’s alpha with a high significant result of 0.911 (0.902-0.913)> r table was obtained. In conclusion, the Indonesian PFDI-20 questionnaire is valid and reliable, thereforeit can be used in Indonesian population.